Lingering effects associated with the consumer use of virtual reality - Porter III, John; Robb, Andrew (Frontiers in Virtual Reality, 2022)
Since the release of the Oculus Rift CV1 in 2016, millions of VR headsets have made their way into consumers’ homes. Since then, users have created large quantities of data about their experiences in VR through posts made to online discussion forums. We examine this data to gain insights on what sorts of “lingering effects” users report having experienced after VR, and on the progression of these effects over time. We found three major categories of lingering effects (besides simulator sickness) during our qualitative analysis: perceptual effects, behavioral effects, and changes in dreams. The perceptual and behavioral categories were further divided into sub-themes: disruption of body ownership and proprioception, loss of a sense of depth in the real world, visual aftereffects, the need to verify the reality of the real world through touch, hesitation when moving in the real world, and attempts to apply VR interaction metaphors to real life interactions. Users were nearly unanimous that these lingering effects only occurred after spending at least 1 h in VR, and that these effects completely disappeared several weeks after they first appeared (assuming the user continued to spend time in VR). There was less agreement about how long these effects lasted after exiting a specific VR session. The results of our analysis suggest that users feel that there are no long-term side effects to the use of VR. We pair this analysis with an analysis of interviews conducted with 20 novice users who were loaned Oculus Quest HMDs to use for 4 weeks. Semi-structured interviews with participants further substantiated the findings of our analysis of online discussions.